Effect of active learning versus traditional lecturing on the learning achievement of college students in humanities and social sciences: a meta-analysis - Kozanitis, Anastassis; Nenciovici, Lucian (Higher education, 2023)
A previous meta-analysis found that active learning has a positive impact on learning achievements for college students in STEM fields of study. However, no similar meta-analyses have been conducted in the humanities and social sciences. Because major dissimilarities may exist between different fields or domain of knowledge, there can be issues with transferring research findings or knowledge across fields. We therefore meta-analyzed 104 studies that used assessment scores to compare the learning achieved by college students in humanities and social science programs under active instruction versus traditional lecturing. Student performance on assessment scores was found to be higher by 0.489 standard deviations under active instruction ( Z = 6.521, p < 0.001, k = 111, N = 15,896). The relative beneficial effect of active instruction was found to be higher for some course subject matters (i.e., Sociology, Psychology, Language, Education, and Economics), for smaller (≤ 20 students) rather than larger class or group sizes, and for upper level rather than introductory courses. Analyses further suggest that these findings are not affected by publication bias.